PENGARUH IKLIM ORGANISASI DAN SISTEM REWARD TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL PADA CV. WIRACANA - Mahendra, I Kadek; Subudi, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.04.TAHUN 2019DO - 10.24843/EEB.2019.v08.i04.p04, 2019)
Competition that occurs between companies in the era of globalization requires companies to continue to make improvements or a change in order to remain competitive. The purpose of the study was to analyze the influence of organizational climate and reward system on job satisfaction and organizational commitment. The sample was determined by 86 people with saturated sampling techniques. Data collection is done by distributing questionnaires directly to CV employees. Wiracana and analyzed using calculative descriptive statistics and descriptive statistics in the form of classic assumption tests and path analysis. The results of data analysis show that organizational climate variables and reward systems have a positive and significant effect on job satisfaction. The organizational climate, reward system and job satisfaction have a positive and significant effect on organizational commitment on CV.Wiracana.